Hydrodynamic Process of Partial and en Masse Dam Failure Induced Debris Flows - Shu, Anping; Wang, Le; Zhu, Fuyang; Zhu, Jiapin; Pi, Chengling; Zhang, Ziru; Christian, Huarez (Frontiers in Environmental Science, 2022)
Because of landslide, seismic events and/or unregulated human activities, a massive amount of loose solid materials are sometimes deposited at the confluence between the branch valley and stem stream or blocked at the lateral channel contraction section in a river channel, immersion of these granular materials in naturally-generated reservoir tend to cause mass failure and even induce debris flow. However, the majority of previous studies primarily focused on post-event processes (i.e. flow hydraulics such as flood flow hydrographs, sediment transport or erosion, and river morphological changes) following dam failure. In this study, our attention is restricted to hydro-sediment dynamic processes that control unconsolidated dam failure as well as subsequent debris flow. This objective is achieved by conducting a series of experiments in a tilting flume and selecting the overtopping flows, vertical grading configurations, dam heights, and channel gradients as causative factors responsible for chain disaster in form of dam failure and debris flow. We found that all experimental dams are either subject to partial failure through a gradual breach development or suddenly collapsed in en masse failure mode, debris flows induced by partial dam failures are likely to take place in the conditions of low overtopping flow and shallow channel slope. On the contrary, debris flows originated from en masse dam failures are shown to well develop in the opposite conditions. Also, the critical shear stresses for sediment entrainment under en masse dam failure cases are generally higher if compared with partial dam-failure equivalents. Moreover, the relative proportion of clear water to erodible solid materials is also related with dam failure mode, which will eventually determine debris-flow properties. These findings have strong implications for predicting and mitigating natural disaster of these kinds usually encountered in nature.